Prehabilitation of dysphagia in the therapy of head and neck cancer- a systematic review of the literature and evidence evaluation - Vester, Sarah; Muhr, Anna; Meier, Johannes; Süß, Christoph; Kummer, Peter; Künzel, Julian (Frontiers in Oncology, 2023)
Background Prehabilitation is becoming increasingly important in oncology because of the significant survival benefits that the reduction of malnutrition provide. Specifically, tumor- and therapy-related dysphagia leads to malnutrition in more than half of head and neck tumor patients. Studies describe the positive effects of an early onset of swallow-specific prehabilitation on the protection of the swallowing function. This paper intents to evaluate the existing evidence on the efficacy of preventive forms of swallowing therapy. Methods A systematic literature search was performed in February 2022 in the Cochrane Library, MEDLINE via PubMed, and ClinicalTrials.gov databases for randomized controlled trials investigating preventive swallowing therapy in head and neck tumor patients. This Procedure complies with the PRISMA statement. The RCTs were evaluated by using the PEDro Scale and the Cochrane Risk of Bias tool RoB2. Results Five randomized-controlled trials with 423 participants were identified. Four Studies showed moderate to high quality in the PEDro analysis, one showed less. The risk of bias was high in all studies because there was no possibility for blinding and there were high dropout rates. Heterogeneity in interventions, measurement instruments, measurement time points, and outcomes limits a general statement about which swallowing exercises are suitable for the prevention of dysphagia in head and neck tumor patients. Evidence is provided for short-term effects (≤24 months) on functional aspects of swallowing and quality of life. Overall, a decreasing adherence over time was observed in the intervention groups. Discussion Initial studies describe swallowing-specific prehabilitation programs in head and neck tumor patients as effective, at least in the short term, whereas long-term effects need to be further investigated. At the current time the evidence base for clear recommendations does not appear to be sufficiently high and studies share a high risk of bias. Further well-designed research, especially considering the conditions in the national health care system, is needed. Other There was no funding and no registration.